King George and the ducky - Nawrocki, Michael; Vischer, Lisa.; Vischer, Phil.; Big Idea Productions ([United States] : Word Entertainment [distributor], 2003)
Unlike other kings, King George spends most of his time in the bath tub, because that is where his favorite toy is - a rubber ducky. But just one ducky isn't enough for King George ... he wants them all. Discover what happens when the king decides that he is the most important person above all others. Learn that whether you are a king or a kid, God wants us all to think of others first.
DVD; Dolby digital 5.1 surround sound.
"A lesson about ... selfishness"--Container.
Originally released as a television show in 2000.
Voices: Mike Nawrocki, Lisa Vischer, Phil Vischer.
Bonus features: chapter selects of favorite scenes; audio commentary; behind the scenes features; progression reel; King George and the ducky trivia; how to draw Junior Asparagus, ducky; art gallery; trailers; Madame Blueberry storybook; veggie karaoke; castle maze; cast bios; family fun activity; DVD-ROM content; subtitles; "Easter Eggs"(hidden features).
Special bonus feature: Endangered love.
Keywords: Selfishness -- Juvenile drama; Vegetables -- Juvenile drama; Rubber toys -- Juvenile drama; Rubber toys; Selfishness; Vegetables; Video recordings for the hearing impaired; Short films; Animated films; Children's films; Drama; Juvenile works